Neurological involvement of IgG4-related disease: description of a case and review of the literature - Varrassi, Marco (Neuroradiol J, 2017)
IgG4-related disease is a recently discovered pathological entity, histologically characterised by fibrosis and IgG4-positive plasma cell infiltration. This condition may virtually involve every site of the organism, with a various range of clinical presentations. The most commonly affected organ is the pancreatic gland, but it can also involve the biliary tract, salivary and lacrimal glands, kidneys, orbital tissues, lymph nodes, lungs and many others. More recently, IgG4-related disease has been demonstrated to involve, in rare cases, also the central nervous system, with a pattern mainly characterised by hypertrophic pachymeningitis. In this paper we evaluated the clinical and magnetic resonance imaging features of the IgG4-related disease in the central nervous system, reporting a case of brain and spinal cord involvement. In our case, in fact, a 62-year-old man complaining of paresthesia, burning dysesthesia and severe hyposthenia in the lower limbs presented with inflammatory pseudotumour with orbital involvement and focal dural and spinal root thickening.